Potency Of Vigna Angularis Against Erα Through In Silico Studies - dini damayanti (Jurnal Kesehatan Islam : Islamic Health Journal, 2020)
Vigna angularis, from the legume family, contains phytoestrogens. Phytoestrogens can activate estrogen receptors and are safer than estrogen. The study aims to analyze the potential of Vigna angularis as an activator of estrogen receptor-α (ERα) through in silico studies. The analysis of molecular docking used SAR (Structure Activity Relationship). A previous study has shown that Vigna angularis contains isoflavones such as Genestein (0.5%), daidzein (14.9%), glycitein (25.8%), formononetin (13%), and biochanin A (45.5%). The results of molecular docking to ERα show that genestein has a free energy binding value of -9.3 and the same amino acid structure, with a control level over estrogen of 66%. In conclusion, in silico studies have shown that genestein from Vigna angularis is the main component that activates the ERα.